Designing for agency and voice: A review of creative and experiential out-of-school programs - Erica D’Souza; Amabel Hunting; Ricardo Sosa; Cheryl Ware; Loïc Le Dé; Andrew Gibbons (Social and Emotional Learning: Research, Practice, and Policy)
Traditionally, Out-of-School Time (OST) programs sought to provide childminding facilities and supplementary academic support to youth. However, they have evolved to deliver programs that support positive youth development with hands-on inquiry to not only support children and adolescents through key developmental stages but to also navigate socio-political challenges. This scoping review investigates creative and experiential OST programs, their design practices and subsequent outcomes. Results from 40 articles highlight the varied, strengths-based practices which centre around increasing participant involvement in decision-making by emphasising flexibility and choice, while staff work collaboratively alongside them. However, for most, rigorous evaluation was lacking and most studies failed to substantiate their claims of fulfilling the development of voice and agentic identity in youth. Future evaluations must ensure they provide evidence of correlating program design with observed outcomes.